An unusual presentation of neonatal rhabdomyosarcoma: a case report - Strah, Danielle; Stanley, Kelly; Oatmen, Kelsie; Kylat, Ranjit I.; Dishop, Megan; de la Maza, Michelina (Frontiers in Pediatrics, 2023)
A full-term infant with unremarkable prenatal course presented at birth with a large midline facial mass and smaller masses in the head and neck. Additionally, multiple diffuse flesh-colored nodules spread along all the upper and lower limbs. Extensive evaluation to cover a broad differential diagnosis of infectious, lymphatic/vascular, and oncologic etiology was undertaken. The initial suspicion was confirmed by biopsy of the skin lesion as congenital alveolar rhabdomyosarcoma. Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcoma of childhood, however neonatal RMS is exceedingly rare. Her initial treatment included vincristine, dactinomycin, and cyclophosphamide in addition to salvage ifosfamide and etoposide which were dose adjusted for age. Herein we describe the presentation of an infant with RMS who had initial improvement before relapsing and succumbing to her disease at five months of age. A review of the limited literature available of this rare condition and newer treatment regimens with improving mortality is described.